Farmer to farmer education: learnings from an international study tour. Issue 5 (4th July 2021) - Hainzer, Kirt; O'Mullan, Catherine; Bugajim, Christian; Brown, Philip Hugh
ABSTRACT: The article captures the perceived impacts of participation in an international study tour (IST). Using interpretive case-based methodology, the article explored how participation has contributed to improved management practices relating to sweet potato production and marketing in Papua New Guinea. Findings from the paper provide insight into how a thoughtfully designed IST incorporating social cohesion can support practice change and development outcomes within agricultural development projects. Further research into how an IST and its design can incite practice change in other contexts is recommended.